Does observing hand actions in animations and static graphics differentially affect learning of hand-manipulative tasks?. (November 2019) - de Koning, Björn B.; Marcus, Nadine; Brucker, Birgit; Ayres, Paul
Abstract: Research shows that animations yield higher learning outcomes than static graphics when learning hand-manipulative tasks such as knot tying. This study investigated whether this superiority of animations is related to observation of the hands in the visualizations. Additionally, it was investigated whether participants' spatial ability influences learning with(out) hands in animations and static graphics. One-hundred participants studied (between-subjects) visualizations (animation vs. static graphics) that did or did not show hands when learning to tie two knots. Participants performed a motor skills task (knot tying proficiency), a cognitive task (reasoning about knot tying process), and indicated cognitive load (after learning and testing). Results showed that animations yielded higher performance (motor skills and cognitive task) and lower cognitive load than static graphics. Observation of hands was detrimental to cognitive task performance. Spatial ability facilitated learning from animations but did not interact with observation of hands. Implications of the results are discussed. Highlights: Animations outperform static graphics when learning hand-manipulative tasks. We investigated whether observation of hands drives the superiority of animation. Results showed that observing hands was detrimental to cognitive performance. Spatial ability facilitated learning from animations with and without hands.